Validation of Psomizopelma metallicum Gibson, 2018 (Hymenoptera: Eupelmidae) - Gibson, Gary A.p. (Zootaxa, 2018)
Gibson (2018) recently revised the species of Psomizopelma Gibson, 1995 (Hymenoptera: Eupelmidae), in which P. metallicum was described based on females as one of four new species. In the section on “type material” for this species, one paratype was stated as deposited in the CNC (Canadian National Collection of Insects, Arachnids and Nematodes, Agriculture and Agri-Food Canada, Ottawa, ON, Canada), whereas the holotype and three other paratypes were stated as deposited in UCFC (University of Central Florida Collection of Arthropods, Orlando, FL, USA). The coden CNC, including the name of the collection and its location was listed in the methods section, but unfortunately the coden UCFC and its relevant collection and location data was inadvertently omitted. As such, under Article 16.4.2 of the International Code of Zoological Nomenclature, the name Psomizopelma metallicum Gibson is not available, because even though a museum coden was given in the publication for where the holotype is deposited, the name and location of the collection was not. The purpose of this correspondence is to correct the oversight in Gibson (2018) and to make the name P. metallicum available. The method of citing holotype label data and abbreviations for structure given below as well as a comprehensive description and illustrations of the species are given in Gibson (2018).